Personality profile of women practising contact sports using the example of karate kyokushin competitors and handball players - Piepiora, P.; Petecka, A. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2020)
Background and objective. Differences in the psyche of sportsmen and sportswomen are ambiguous. However they can be seen in contact sports. This study has been an attempt at evaluating the personality profile of women practising contact sports. Material and methods. The study involved the best Polish female karate kyokushin competitors (n=30) and female handball players (n=30) aged 20-29. The method incorporated the use of the NEO-FFI questionnaire. The statistical analysis was made with Statistica 13.1 software. Results. The female karate kyokushin competitors and female handball players differ from each other (raw score) on the scales of extraversion, openness to experience and conscientiousness. In sten scores, on the other hand, the significant difference between the groups studied was only at the scale of openness to experience. Conclusions. The personality profile of the female contact sports competitors incorporates average neuroticism, extroversion, openness to experience and compliance as well as high conscientiousness. The differences in the personality scales are a result of the specific nature of the sports discipline, individual or team sports, practised. The personality indicator which differentiates men from women is neuroticism.